The Medieval Origins of Commandaria - Weaver, William Woys (Petits Propos Culinaires, 2008)
The author examines the history of Commandaria, the legendary sweet wine from Cyprus commonly understood to be the denomination with the longest continuous identity of any wine in Europe.